Crosstalk between TBK1/IKKε and the type I interferon pathway contributes to tubulointerstitial inflammation and kidney tubular injury - Córdoba-David, Gina; García-Giménez, Jorge; Cardoso Castelo-Branco, Regiane; Carrasco, Susana; Cannata, Pablo; Ortiz, Alberto; Ramos, Adrián M. (Frontiers in Pharmacology, 2022)
The type I interferon (T1-IFN) pathway regulates innate immunity, inflammation, and apoptosis during infection. However, the contribution of the T1-IFN pathway or upstream signaling pathways to tubular injury in kidney disease is poorly understood. Upon observing evidence of activation of upstream regulators of the T1-IFN pathway in a transcriptomics analysis of murine kidney tubulointerstitial injury, we have now addressed the impact of the T1-IFN and upstream signaling pathways on kidney tubulointerstitial injury. In cultured tubular cells and kidney tissue, IFNα/β binding to IFNAR activated the T1-IFN pathway and recruited antiviral interferon-stimulated genes (ISG) and NF-κB-associated proinflammatory responses. TWEAK and lipopolysaccharide (LPS) signaled through TBK1/IKKε and IRF3 to activate both ISGs and NF-κB. In addition, TWEAK recruited TLR4 to stimulate TBK1/IKKε-dependent ISG and inflammatory responses. Dual pharmacological inhibition of TBK1/IKKε with amlexanox decreased TWEAK- or LPS-induced ISG and cytokine responses, as well as cell death induced by a complex inflammatory milieu that included TWEAK. TBK1 or IRF3 siRNA prevented the TWEAK-induced ISG and inflammatory gene expression while IKKε siRNA did not. In vivo, kidney IFNAR and IFNβ were increased in murine LPS and folic acid nephrotoxicity while IFNAR was increased in human kidney biopsies with tubulointerstitial damage. Inhibition of TBK1/IKKε with amlexanox or IFNAR neutralization decreased T1-IFN pathway activation and protected from kidney injury induced by folic acid or LPS. In conclusion, T1-IFNs, TWEAK, and LPS engage interrelated proinflammatory and antiviral responses in tubular cells. Moreover, inhibition of TBK1/IKKε with amlexanox, and IFNAR targeting, may protect from tubulointerstitial kidney injury.